2022
DOI: 10.1096/fj.202101699r
|View full text |Cite
|
Sign up to set email alerts
|

The functionality and translatability of neocartilage constructs are improved with the combination of fluid‐induced shear stress and bioactive factors

Abstract: Neocartilage tissue engineering aims to address the shortcomings of current clinical treatments for articular cartilage indications. However, advancement is required toward neocartilage functionality (mechanical and biochemical properties) and translatability (construct size, gross morphology, passage number, cell source, and cell type). Using fluid‐induced shear (FIS) stress, a potent mechanical stimulus, over four phases, this work investigates FIS stress’ efficacy toward creating large neocartilage derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
(254 reference statements)
0
2
0
Order By: Relevance
“…The research demonstrated the effect of FIS stress stimulation across sources of bovine and minipig cells. In addition, when FIS stress was added to bioactive factors, advancement in mechanical and biochemical properties was evident, with increased shear modulus by 115% compared to bioactive factor-only controls ( Figure 4A ) ( Salinas et al, 2022 ). Histologically, samples treated with bioactive substances and FIS stress showed stronger Saf O staining, which is a sign that the neocartilage structures contain more glycosaminoglycans ( Figure 4B ), and similar staining intensities using H&E ( Figure 4C ).…”
Section: Classification and The Influence Of Mechanical Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…The research demonstrated the effect of FIS stress stimulation across sources of bovine and minipig cells. In addition, when FIS stress was added to bioactive factors, advancement in mechanical and biochemical properties was evident, with increased shear modulus by 115% compared to bioactive factor-only controls ( Figure 4A ) ( Salinas et al, 2022 ). Histologically, samples treated with bioactive substances and FIS stress showed stronger Saf O staining, which is a sign that the neocartilage structures contain more glycosaminoglycans ( Figure 4B ), and similar staining intensities using H&E ( Figure 4C ).…”
Section: Classification and The Influence Of Mechanical Stimulimentioning
confidence: 99%
“… Using bioactive factors and FIS stress to improve neocartilage (A) Exogenous TGF-1 and FIS stress may enhance ECM content in a comparable way. Further research and combination with other mechanical stimulation regimens are encouraged in the hopes of further improving the functional properties of neocartilage by studies about additional bioactive factors, such as transforming growth factor beta 1 (TGF-β1), chondroitinase ABC (C-ABC), lysyl oxidase-like 2 (LOXL2), polycystin 1/2(PC1/2), and cytochalasin D ( Salinas et al, 2022 ). (B–D) The intensity of glycosaminoglycan staining is increased when bioactive substances and FIS stress are combined.…”
Section: Classification and The Influence Of Mechanical Stimulimentioning
confidence: 99%